2019
DOI: 10.1002/sctm.18-0141
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin Sulfate Glycosaminoglycan Scaffolds for Cell and Recombinant Protein-Based Bone Regeneration

Abstract: Bone morphogenetic protein 2 (BMP‐2)‐loaded collagen sponges remain the clinical standard for treatment of large bone defects when there is insufficient autograft, despite associated complications. Recent efforts to negate comorbidities have included biomaterials and gene therapy approaches to extend the duration of BMP‐2 release and activity. In this study, we compared the collagen sponge clinical standard to chondroitin sulfate glycosaminoglycan (CS‐GAG) scaffolds as a delivery vehicle for recombinant human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 69 publications
(85 reference statements)
1
26
0
Order By: Relevance
“…CS has been used for sustained delivery of BMPs in the form of coatings [114] and scaffolds [7476]. A CS-based scaffold was compared to collagen sponges (the standard clinical delivery method) as BMP-2 delivery systems.…”
Section: Gag-mediated Delivery Of Growth Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…CS has been used for sustained delivery of BMPs in the form of coatings [114] and scaffolds [7476]. A CS-based scaffold was compared to collagen sponges (the standard clinical delivery method) as BMP-2 delivery systems.…”
Section: Gag-mediated Delivery Of Growth Factorsmentioning
confidence: 99%
“…A CS-based scaffold was compared to collagen sponges (the standard clinical delivery method) as BMP-2 delivery systems. In vitro extended release of 7 μg of BMP-2 over 16 days was observed in the CS scaffold but not the collagen sponge, stimulating bone formation in a critically sized femoral defect in rats [74]. CS-collagen scaffolds were coated with poly-L-lactide (PLLA) and sucrose acetate isobutyrate to extend the release of BMP-2, resulting a release of 50% of growth factor over 15 days.…”
Section: Gag-mediated Delivery Of Growth Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the clinical potential of this strategy and move toward the development of an injectable biologic therapy for large bone defect healing in humans, Andrews et al next evaluated bone regeneration using a chondroitin sulfate glycosaminoglycan scaffold for the delivery vehicle for recombinant human (rh) BMP‐2 and BMP‐2 overexpressing MSCs. Writing in STEM CELLS Translational Medicine , the authors initially discovered extended BMP‐2 release from the chondroitin sulfate glycosaminoglycan (GAG) scaffold when compared with a collagen sponge (Col), the currently used clinical gold standard for bone regeneration. The administration of this newly developed strategy within electrospun polycaprolactone nanofiber meshes to increase retention within the defect and enhance BMP‐2 delivery permitted comparable bone formation in critically sized femoral defects in model rats as measured by bone volume, strength, and stiffness when again compared with the collagen sponge.…”
Section: Related Articlesmentioning
confidence: 99%
“…In our second Featured Article published this month in STEM CELLS , Zhou et al describe a synergistic interaction between Krüppel‐like factor 2 (KLF2)‐expressing human (h)MSCs and endothelial cells that may significantly influence future bone regeneration and vascular network bioengineering strategies . In a Related Article recently published in STEM CELLS Translational Medicine , Andrews et al compared bone repair techniques and demonstrated the utility of a bone morphogenetic protein 2 (BMP‐2)‐releasing chondroitin sulfate glycosaminoglycan scaffold as a means to support large bone defect healing by engineered MSCs …”
mentioning
confidence: 99%